Correlation between topological band character and chemical bonding in a Bi14Rh3I9-based family of insulators - Rasche, Bertold; Isaeva, Anna; Ruck, Michael; Koepernik, Klaus; Richter, Manuel; Van Den Brink, Jeroen (Scientific Reports, 2016)
Recently the presence of topologically protected edge-states in Bi 14 Rh 3 I 9 was confirmed by scanning tunnelling microscopy consolidating this compound as a weak 3D topological insulator (TI). Here, we present a density-functional-theory-based study on a family of TIs derived from the Bi14Rh3I9 parent structure via substitution of Ru, Pd, Os, Ir and Pt for Rh. Comparative analysis of the band-structures throughout the entire series is done by means of a unified minimalistic tight-binding model that evinces strong similarity between the quantum-spin-Hall (QSH) layer in Bi14Rh3I9 and graphene in terms of-molecular orbitals. Topologically non-trivial energy gaps are found for the Ir-, Rh-, Pt-and Pd-based systems, whereas the Os-and Ru-systems remain trivial. Furthermore, the energy position of the metal-band centre is identified as the parameter which governs the evolution of the topological character of the band structure through the whole family of TIs. The-band position is shown to correlate with the chemical bonding within the QSH layers, thus revealing how the chemical nature of the constituents affects the topological band character.
CRIS-Team Scopus Importer:2023-03-20